Correlation Analysis between Household Hygiene and Sanitation and Nutritional Status and Female Leprosy in Gresik Regency - Flora Ramona Sigit Prakoeswa; Afik Zakie Ilhami; Ratna Luthfia; Aviola Syania Putri; Hardyanto Soebono; Dominicus Husada; Hari Basuki Notobroto; Muhammad Yulianto Listiawan; Anang Endaryanto; Cita Rosita Sigit Prakoeswa (Hindawi Limited, 2020)
Leprosy, also known as morbus Hansenʼs disease, is a chronic disease caused by M. leprae. Leprosy attacks various parts of the body including nerves and skin. The most important factor in the occurrence of leprosy is the sources of transmission and contact, both from patients and the environment. Household conditions where the person lives and the nutritional status of the individual can be a risk factor for leprosy. Household hygiene and sanitation can be seen from several aspects, like the physical environment of the house, clean water facilities, personal hygiene, availability of latrines, waste disposal facilities, and garbage disposal. This study was aimed to determine the correlation between household hygiene sanitation and nutritional status with females with leprosy in Gresik Regency. This case-control study was conducted in December 2019 in Gresik Regency. The subjects of this study were 74 respondents taken by consecutive sampling techniques. Retrieval of data was carried out using observations from the healthy house component questionnaire, personal hygiene questionnaire, and direct measurement. Data were analyzed using the chi-square test. The results showed significant correlation between physical environment of the house (p=0.001, OR = 0.104), clean water facilities (p=0.008, OR = 0.261), availability of latrines (p=0.018, OR = 0.209), waste disposal facilities (p=0.015, OR = 0.291), and personal hygiene (p=0.001, OR = 2.850) and female leprosy in Gresik Regency. There is no correlation between nutritional status (p=0.085, OR = 0.422) and wastewater disposal waste (p=0.183, OR = 0.486) and female leprosy in this study.